Loss of nidogen-1 causes lung basement membrane defects and increased metastasis - Xia, Tian; Zornhagen, Kamilla W.; Miinalainen, Ilkka; Abramovitz, Lilach; Madsen, Chris D.; Nicolau, Monica; Mayorca-Guiliani, Alejandro E.; Erez, Neta; Erler, Janine T. (Frontiers in Immunology, 2025)
Metastasis is the most common cause of cancer patient deaths. It is a complex process strongly influenced by the extracellular matrix (ECM). A mass spectrometry analysis comparing ECM proteins from healthy mouse lungs versus metastatic lungs has previously been performed, and the basement membrane (BM) component nidogen-1 has been identified to be one of the most downregulated ECM proteins in metastatic lungs. Here, we investigated the role of stromal cell-derived nidogen-1 in metastasis. We found that nidogen-1 is expressed by fibroblasts but not cancer cells, and nidogen-1 is downregulated in breast tumors compared to healthy mammary gland. Using the HCmel12 melanoma model, we found that loss of stromal nidogen-1 causes increased lung metastasis. Using electron microscopy, we found that nidogen-1 knockout mice have defects in the lung alveoli, such as fragmented endothelium, poorly defined BM, and enlarged interstitium. This suggests that loss of nidogen-1 may cause BM defects, which compromise its barrier function, thereby increasing the ability of cancer cells to extravasate and colonize the lungs. Our findings provide novel insight into cancer-stromal interplay and the role of nidogen-1 at the metastatic niche.